(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background Mental health disorders may lead to oxidative stress and increased the risk for other disease which may be controlled by yoga.Objectives This study was performed to observe the influence of yogic practice on oxidative stress- antioxidant levels in persons with mental health disorders.Methods A total of four hundred thirty (n = 430) adult male volunteers (age 21–50 years) screened, and were grouped into (a) mental health disorders group (MHDG, n = 230) and control group (CG, n= 200) 80 from MHDG and 50 from CG were excluded. The remaining 150 volunteers of MHDG and 150 volunteers of CG spited up (i) 21-30 yrs (Category-I) (n = 50), (ii) 31-40 yrs (Category-II) (n = 50), and (iii) 41-50 yrs (Category-III) (n=50). The MHDG followed a yoga training of 60 minday, 5 daysweek for 12 weeks yogic practice was prohibited in CG. Oxidative stress biomarkers and antioxidant levels were assessed in both the groups at the beginning (0-week) and after 12-weeks of intervention.Results A lower level of MDA and higher in SOD, CAT, GPx, vit E and vit C levels were noted among the subjects of MHDG following 12 weeks of yoga training when compared to base line (0 week). Further, significantly higher level of MDA, lower level of SOD, CAT, GPx, vitamin E and vitamin C were observed among the subjects of MHDG when compared to CG at the beginning (0 week) and after 12 weeks of the study. In addition, age wise difference in MDA, SOD, CAT, GPx, vitamin E and vitamin C was also observed among the subjects of mental health disorder group and control group.Conclusion Regular practice of yoga improves the oxidative stress-antioxidant levels and reduced the risk of various diseases among the persons with mental health disorders.